The research of an art form of the performance on the modern stage (Herald of Journalism, 2016)
The article is devoted to searching the relevant form of the modern theater trends in Kazakhstan. Analyzing the performances which realized by leading, modern director Robert Wilson, Alvis Hermanis, Aubakir Rahimov in the theaters of Germany, Switzerland, Kazakhstan, the author reveals the problem of searching for an art form on the modern stage.
Keywords: modern theater; art form